Complexometric Determination of Tl(III) Using Thiocarbohydrazide as a Replacing Reagent - Narayana, B.; Lucos Jose, P.; Karunakaran, V.; Gajendragad, M.R. (Asian Journal of Chemistry, 2010)
A simple and selective complexometric method using masking and demasking techniques is proposed for the determination of thallium(III). In presence of diverse metal ions thallium(III) is complexed with a known excess of EDTA and the uncomplexed EDTA is back titrated (pH, 5–6, hexamine) with lead nitrate solution, using xylenol orange as indicator. Thiocarbohydrazide (TCH) solution in water is then added and the liberated EDTA from the Tl-EDTA complex is titrated against lead solution. Reproducible and accurate results are obtained in the concentration range 2–61 mg of thallium with relative error of < 0.05% and standard deviation of < 0.04.